Mechanical forces in lymphatic vessel development: Focus on transcriptional regulation - Ujiie, Naoto; Kume, Tsutomu (Frontiers in Physiology, 2022)
The lymphatic system is crucial for the maintenance of interstitial fluid and protein homeostasis. It has important roles in collecting excess plasma and interstitial fluid leaked from blood vessels, lipid absorption and transportation in the digestive system, and immune surveillance and response. The development of lymphatic vessels begins during fetal life as lymphatic endothelial progenitor cells first differentiate into lymphatic endothelial cells (LECs) by expressing the master lymphatic vascular regulator, prospero-related homeobox 1 (PROX1). The lymphatic vasculature forms a hierarchical network that consists of blind-ended and unidirectional vessels. Although much progress has been made in the elucidation of the cellular and molecular mechanisms underlying the formation of the lymphatic vascular system, the causes of lymphatic vessel abnormalities and disease are poorly understood and complicated; specifically, the mechanistic basis for transcriptional dysregulation in lymphatic vessel development remains largely unclear. In this review, we discuss the recent advances in our understanding of the molecular and cellular mechanisms of lymphatic vascular development, including LEC differentiation, lymphangiogenesis, and valve formation, and the significance of mechanical forces in lymphatic vessels, with a focus on transcriptional regulation. We also summarize the current knowledge on epigenetic mechanisms of lymphatic gene expression.